Simultaneously enhanced strength and ductility for 3D-printed stainless steel 316L by selective laser melting - Sun, Zhongji (2018)
Laser-based powder-bed fusion additive manufacturing or three-dimensional printing technology has gained tremendous attention due to its controllable, digital, and automated manufacturing process, which can afford a refined microstructure and superior strength. However, it is a major challenge to additively manufacture metal parts with satisfactory ductility and toughness. Here we report a novel selective laser melting process to simultaneously enhance the strength and ductility of stainless steel 316L by in-process engineering its microstructure into a <011> crystallographic texture. We find that the tensile strength and ductility of SLM-built stainless steel 316L samples could be enhanced by ~16% and ~40% respectively, with the engineered <011> textured microstructure compared to the common <001> textured microstructure. This is because the favorable nano-twinning mechanism was significantly more activated in the <011> textured stainless steel 316L samples during plastic deformation. In addition, kinetic simulations were performed to unveil the relationship between the melt pool geometry and crystallographic texture. The new additive manufacturing strategy of engineering the crystallographic texture can be applied to other metals and alloys with twinning-induced plasticity. This work paves the way to additively manufacture metal parts with high strength and high ductility.